Transverse fastening reinforcement of sandwich panels with upcycled bottle caps core. (March 2021) - Oliveira, PR; da Silva, LJ; Panzera, TH; del Pino, GG; Scarpa, F
This work describes the use of transverse reinforcement in eco-friendly sandwich panels made from aluminium skins and a core of upcycled bottle caps. The Design of Experiments technique identifies the effect of the position of the metal rivets on the panel. The results show a moderate increase in strength and a significant enhancement of the sandwich panel stiffness when the rivets are placed on the upper skin, with a remarkable improvement in terms of the core shear modulus. The use of metal rivets has also increased the specific mechanical strength and stiffness of the panels, which highlights the effectiveness of the transverse reinforcement in bottle caps panels.